Bahan-bahan perhubungan media: dari organisasi ke media massa di Malaysia - Mohd Yahya Mohamed Ariffin; Md. Sidin Ahmad Ishak (Penerbit UKM, 2010)
The main objective of this paper is to examine the contents of media relations materials received by the mass media industry in Malaysia. Media relations materials are pivotal tools in public relations industries. The usage of such materials for the purpose of marketing communications are deemed effective, successful, hassle free and inexpensive. The content analysis method is used to analyze media communications materials received from various organizations. A total of 420 materials related to public relations were gathered from two media organizations. Research findings show that these materials received by the two media are from various categories of public and private organizations. Findings also prove that the contents of media relations materials were dominated by social and economic issues in comparison to other issues. Most of these media relations materials contain important information needed by the mass media, such as the name of the organizations, phone and facsimile numbers, e-mail and website addresses.